Enabling Environment to Scale AWD and Rice Straw Management: A 6-Step Approach - Nelson, Katherine; Tran, Nguyen Bao; Cuong, Ong Quoc; Trang, Vu Hong (CGIAR System Organization, 2024)
Alternate wetting and drying (AWD) and rice straw management are critical mitigation actions to transition to low emission food systems. This report investigates the enabling environment necessary to out scale AWD and low-emission rice straw management practices, employing a structured 6-step approach to scaling developed by the CGIAR Initiative on Low Emission Food Systems. Through source identification, analysis of government priorities, adoption potential evaluation, upgrading strategy development, business model design, and climate action measurement, stakeholders can foster the widespread adoption of sustainable and low-emission rice practices, thus contributing to mitigating climate change and enhancing agricultural sustainability.